The diagnostic performance of whole-body MRI in the staging of lymphomas in adult patients compared to PET/CT and enhanced reference standard-systematic review and meta-analysis - Lambert, Lukas; Burgetova, Andrea; Trneny, Marek; Bircakova, Bianka; Molinsky, Jan; Benesova, Katerina; Zogala, David; Michalek, Pavel (Quantitative imaging in medicine and surgery, 2022)
Background: Morphology highlighted by diffusion weighted imaging (DWI) is the basis of whole-body MRI (wbMRI). The aim of this study was to analyze current knowledge on the diagnostic performance of wbMRI in the pretreatment staging of patients with lymphoma. Methods: A search for original articles reporting the diagnostic performance (sensitivity, specificity) of pretreatment (first staging or staging in relapsed patients after complete remission) wbMRI in nodal and extranodal involvement by extracranial lymphoma and the agreement of stage by the Cotswolds-modified Ann Arbor classification in adult patients compared to the reference standard (PET/CT or enhanced reference standard) was conducted in PubMed, EMBASE, Cochrane Library, ClinicalTrials.gov. Results: Altogether 15 studies with 519 patients were included in the meta-analysis. The pooled sensitivity and specificity for nodal involvement were 0.93 (95% CI: 0.90 to 0.96) and 0.99 (95% CI: 0.98 to 1.00). For nodal staging, most studies used the size criterion of 10 mm in the short diameter (n=10) and the absence of prominent fatty hilum (n=4). Restricted diffusion on diffusion-weighted imaging as a sign of nodal involvement was either not used (n=5), used for detection (n=4), semi-quantitatively (n=4), or quantitatively (n=1). Only one study (7) relied solely on restricted diffusion as the main criterion for nodal involvement. The pooled sensitivity and specificity for extranodal involvement were 0.89 (95% CI: 0.79 to 0.98) and 0.99 (95% CI: 0.99 to 1.00). Seven studies considered diffuse splenic involvement when its long or vertical axis was greater than 13 cm regardless of the patient's physiognomy. The pooled agreement in staging (Cohen's kappa) was almost perfect (0.90, 95% CI: 0.84 to 0.95). Discussion: The sensitivity and specificity of wbMRI in the assessment of the nodal and extranodal involvement by lymphoma is high. The agreement of wbMRI with the reference standard is almost perfect.